Brugada Syndrome: Progress in Genetics, Risk Stratification and Management. Issue 1 (March 2019) - Romero, Jorge, Dan L Li, Ricardo Avendano; Diaz, Juan Carlos; Tung, Roderick; Biase, Luigi Di
No abstract available